Anthroposophic Medicine: An Integrative Medical System Originating in Europe. Issue 6 (November 2013) - Kienle, Gunver S.; Albonico, Hans-Ulrich; Baars, Erik; Hamre, Harald J.; Zimmermann, Peter; Kiene, Helmut
Anthroposophic medicine is an integrative multimodal treatment system based on a holistic understanding of man and nature and of disease and treatment. It builds on a concept of four levels of formative forces and on the model of a three-fold human constitution. Anthroposophic medicine is integrated with conventional medicine in large hospitals and medical practices. It applies medicines derived from plants, minerals, and animals; art therapy, eurythmy therapy, and rhythmical massage; counseling; psychotherapy; and specific nursing techniques such as external embrocation. Anthroposophic healthcare is provided by medical doctors, therapists, and nurses. A Health-Technology Assessment Report and its recent update identified 265 clinical studies on the efficacy and effectiveness of anthroposophic medicine. The outcomes were described as predominantly positive. These studies as well as a variety of specific safety studies found no major risk but good tolerability. Economic analyses found a favorable cost structure. Patients report high satisfaction with anthroposophic healthcare.